ACCOUNTING FOR JOINT COSTS. - Avery, Harold G. (The Accounting Review, 1951)
Abstract One must finally conclude that the problem of allocating joint costs per se is unsolvable from a theoretical point of view. It is impossible to determine what costs should be matched against the income resulting from the manufacture of by-products and joint products. Procedures for allocating joint costs are based on certain standards of reasonableness; and the results are justified in the light of present-day market values, productive technology, and business experience. The techniques for the allocation of joint costs must be improved; otherwise, the conclusions obtained from various methods of joint cost distribution have no foundation of proof. Accountants will then have to resort to the basic criterion of all successful business enterprise, namely, that total revenue of the organization-in the long run-must cover the total costs of production.